KAJIAN POTENSI BUDIDAYA RUMPUT LAUT DI PERAIRAN PULAU BUNYU MELALUI PENDEKATAN HIDRO-OCEANOGRAFI DAN SISTEM INFORMASI GEOGRAFI - Jimmy Cahyadi; Asbar Laga; Mas Apriyan Noor (Jurnal Harpodon Borneo, 2010)
The purpose of this research is to study potential sea weed cultivation at island waters bunyu by hidro-oceanografi and geography information system.  Location of this research on marine culture development zone plan waters (RDTR) island bunyu, Regency bulungan, East Kalimantan, where geographically in 3°24'46" -3°24'46" latitude and 117°47'3" -118°00'00" Longitude.  This research are literature review,  ground check, Observation and Interview.  The research that used method survey and qualitative.  The stage is preced with identify condition hidro-oceanografi that measuresed according to insitu as primary data.  Then identification accessibility as secondary data.  Identification result further more at analysis based on weighted  sea weed cultivation location with matrix.  Analysis result above then analyzed furthermore by using method skoring and Geographical information system to produces map tematik new.  Percentage turn result as result skoring from location suitable evaluation system evaluation for sea weed cultivation (eucheuma cottonii) show in four locations moderate suitable and One location marginal suitable Keywords: Sea weed, Hidro-oceanografi, Geographical information system